1996
DOI: 10.1126/science.272.5261.557
|View full text |Cite
|
Sign up to set email alerts
|

Transcription-Coupled Repair Deficiency and Mutations in Human Mismatch Repair Genes

Abstract: Deficiencies in mismatch repair have been linked to a common cancer predisposition syndrome in humans, hereditary nonpolyposis colorectal cancer (HNPCC), and a subset of sporadic cancers. Here, several mismatch repair-deficient tumor cell lines and HNPCC-derived lymphoblastoid cell lines were found to be deficient in an additional DNA repair process termed transcription-coupled repair (TCR). The TCR defect was corrected in a mutant cell line whose mismatch repair deficiency had been corrected by chromosome tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
114
1
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 261 publications
(116 citation statements)
references
References 40 publications
0
114
1
1
Order By: Relevance
“…In particular, MMR recognizes the mismatches in heteroduplex recombination intermediates, preventing completion of recombination between diverged sequences, thus promoting genetic stability (42)(43)(44). More recently, several groups have shown that MMR is involved in the repair of mismatched 8-oxoguanine, which is one of the major base lesions formed after DNA oxidative attack (45), and may participate in the transcriptioncoupled repair pathway (46,47). Cells with a defective MMR show a mutation rate 100-fold greater than that of normal cells, causing the accumulation of potentially deleterious mutations throughout the genome.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, MMR recognizes the mismatches in heteroduplex recombination intermediates, preventing completion of recombination between diverged sequences, thus promoting genetic stability (42)(43)(44). More recently, several groups have shown that MMR is involved in the repair of mismatched 8-oxoguanine, which is one of the major base lesions formed after DNA oxidative attack (45), and may participate in the transcriptioncoupled repair pathway (46,47). Cells with a defective MMR show a mutation rate 100-fold greater than that of normal cells, causing the accumulation of potentially deleterious mutations throughout the genome.…”
Section: Discussionmentioning
confidence: 99%
“…MSI in lung cancer occurs at a low frequency (Benachenhou et al, 1998). However, MMR proteins are involved in a variety of other cellular processes such as homologous recombination (de Wind et al, 1995), mediation of the G2 checkpoint (Meyers et al, 1997;Davis et al, 1998), the signalling pathway and transcriptioncoupled nucleotide excision repair (Mellon et al, 1996). Genedosage effects and reduced expression of MMR proteins have been suggested as risk factors (Wei et al, 1996(Wei et al, , 1998Benachenhou et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a gene dosage effect affecting the stoichiometry and the activity of the heteromolecular mismatch-repair complex may be sufficient to promote cancer by impairing functions other than the correction of replication errors. Mismatchrepair proteins are involved in a variety of vital cellular processes, including the homologous recombination (Jones et al, 1987;deWind et al, 1995), the mediation of the G2 checkpoint (Hawn et al, 1995), transcription-coupled nucleotide excision repair (Mellon et al, 1996) and in the recognition of DNA damage and/or in the signalling pathway contributing to the generation of apoptotic cells (Kat et al, 1993;Mu et al, 1997). Interestingly, the influence of environmental factors on the genome stability in cells defective in nucleotide excision repair and mismatch-repair could be substantial.…”
Section: Discussionmentioning
confidence: 99%